Factors determining the tendency of rural households in Central Pomerania to save – PILOT study results - Agnieszka Strzelecka; Danuta Zawadzka (Polityki Europejskie, Finanse i Marketing)
The aim of this research is to identify factors affecting the propensity of rural households to save, on the example of 100 entities in Central Pomerania, based on pilot studies (direct questionnaire technique) using the logistic regression model. The study assumes that the dependent variable is the occurrence of savings in the household in 2018. The selection of independent variables for the logistic regression model was made on the basis of literature studies. The results of the analysis confirmed that statistically significant parameters for the variables were: average monthly net income per one person in the household, diversification of the income sources and the share of expenses on food and non-alcoholic beverages in total household consumption expenditure. The first two parameters increase the probability of saving by rural households of Central Pomerania. The last of these parameters reduces the chance of deferring consumption through savings.